PENGUATAN PARTISIPATIF GENERASI MUDA DALAM MENDORONG REVOLUSI PERTANIAN BERKELANJUTAN DI DESA TUREKISA - Wuli, Rofinus Neto (Merwinspy Publisher, 2024)
This community service program aimed to foster awareness and active participation of the millennial generation in realizing sustainable agriculture, particularly in Turekisa Village, Ngada Regency. The declining interest of youth in the agricultural sector has become a serious concern, given the looming crisis in farmer regeneration that directly threatens national food security. The program was carried out through the delivery of inspirational content in the form of thematic presentations, participatory discussions, and the promotion of locally developed flagship liquid organic fertilizer (POC) by the Flores Bajawa Agricultural College. The implementation method was educational and persuasive, employing a contextual approach that stimulated critical awareness among participants about the challenges and opportunities in modern agriculture. The results showed that participants especially young people began to recognize the importance of transforming the agricultural sector through the integration of agricultural technology, digital marketing, and innovation in rural economic institutions. The participants' enthusiasm for adopting technology in cultivation, post-harvest management, and online product distribution emerged as an initial indicator of youth readiness to engage in agriculture. Additionally, the introduction of agroforestry concepts, organic farming, and the use of renewable energy provided new insights that were highly appreciated. In conclusion, this community outreach approach targeting the millennial generation through contextual education, technological integration, and inspirational narratives proved effective in cultivating youth involvement in sustainable agricultural development. This strategy should be replicated in other regions with support from educational institutions, government bodies, and farming communities.